Programa de capacitacion para docentes en atención a la diversidad a alumnos con TDAH - Noriega Solari de Ortiz, Heidi Joany (2020)
Currently, teachers need to be trained to address the diversity of students and even more so if they are students with ADHD, the most present disorder in school age (Valda, Suñagua, Coaquira, 2018) and that is often linked to poor academic performance and behavioral prob-lems. This program was aimed at 53 tutors of a public institution in Lima Metropolitana with the purpose of raising awareness in attention to the diversity of students with ADHD, through knowledge of the definitions, the selection of methodological strategies and the contrast be-tween the traditional methodology and that of the model of attention to diversity. The program consists of three stages, the first of knowledge based on Barkley's theory of ADHD, the sec-ond, of management of school strategies based on those proposed by the Peruvian Association of Attention Deficit and a final stage of comparison between the traditional methodology and the attention to diversity. An entry and exit survey was also carried out to corroborate the effectiveness of the program, obtaining positive results in the learning of the tutors, so it is inferred that they have the ability to implement strategies to address the diversity of students with ADHD .